The EU's new era of "Fair Company Taxation": The impact of DEBRA and Pillar Two on the EU Member States' effective tax rates - Emilia Gschossmann; Jost H. Heckemeyer; Jessica Müller; Christoph Spengel; Julia Spix; Sophia Wickel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
The European Commission recently implemented the minimum tax directive (Pillar Two) to ensure that corporate profits are at least taxed at 15%. At the same time, it proposed a legislative initiative aimed at reducing the tax-induced distortions between debt and equity financing (debt-equity bias reduction allowance directive, DEBRA). In our simulation analysis, we evaluate how the two measures and their interplay influence the EU Member States' effective tax levels and thus their location attractiveness. We find that DEBRA, on average, leads to a substantial reduction of the effective tax levels for equity-financed companies. In countries with a combined profit tax rate below 15%, Pillar Two increases the effective average tax burden. The simulation of the interaction of both regulations shows that the effect of Pillar Two dominates that of DEBRA. In addition, the results hold under a common tax base in accordance with the recently proposed "Business in Europe: Framework for Income Taxation" directive (BEFIT).
Keywords: F23; H25; K34; 330; Business in Europe; Framework for Income Taxation; BEFIT; Effective tax rates; Debt-Equity Bias Reduction Allowance; DEBRA; Debt-equity bias; Devereux/Griffith Methodology; Global minimum tax; Pillar Two